Evaluation of the effectiveness of a tertiary course delivered via the World Wide Web : the case of the 86.761 course-- "Learning with computers" : a thesis presented in partial fulfilment of the requirements for the degree of Master in Education at Massey University - Santos, Ieda Margarete (Massey University, 1999)
Delivering courses via the World Wide Web is a relatively new phenomenon. Evidence on how it can promote learning is still under investigation. The main objective of this thesis is to evaluate the effectiveness of a tertiary course, 86.761 "Learning with Computers", delivered via the web, and contribute to the formation of a body of knowledge on this subject. The research is organised into three phases. Phase one involves the design of the web-based course and an interview with the Paper Co-ordinator which documents his perceptions of teaching via the web, the objectives, pedagogical strategies and web tools used to deliver the course content, and the design of the user interface. Phase two of the research describes the implementation of the web-based course. In the third phase, a questionnaire is used to gather data on the students' perceptions of the various aspects of the web-based course. It also involves another interview with the Paper Co-ordinator, which describes his perceptions of teaching via the web, after the implementation of the web-based course. Analysis of data shows that there had been a positive evolution in the Paper Co-ordinator's perceptions of teaching via the web. Regarding the students' perceptions of learning via the web, results suggest that it was a positive and valuable experience, meaning a step in the right direction, yet with plenty of room for improvement. As for the objectives of the web-based course, some were clearly better achieved than others. The pedagogical strategies used to deliver the course content were accomplished with different levels of effectiveness. The results also reveal that the web tools used in the web-based course achieved various degrees of success. Finally, with respect to the user interface, findings show that the web-based course was simple, easy to use and friendly. The aspects of consistency, access and navigation were considered acceptable, yet with plenty of room for improvement. However, the aspects of online help, advice and customisation were considered inadequate. In summary, this thesis was moderately successful in achieving its main objective. More research is needed on how to effectively use the web for teaching and learning.
Keywords: Computer-assisted instruction; Distance education; Internet in education; Online education; Web-based courses